Potential of Mangrove Ecosystem as a Tourism Object Development in Kaledupa Island - Amiruddin Akbar Fisu; Afandi Ahmad; Adrianto Hidayat; Liza Utami Marzaman (Samarinda State Polytechnic, 2020)
Mangrove forests that live in coastal areas, besides being beneficial for human needs, also often clash with development interests such as ports, fish ponds, and tourist areas that threaten their sustainability. Wakatobi Regency has the potential of living natural resources in the form of coastal and marine resources which are quite large, including mangrove ecosystems, seagrass ecosystems and coral reef ecosystems. The purpose of this study is to analyze the potential of mangrove ecosystems and to design the development of mangrove forests as an ecotourism potential. This research is a descriptive-evaluative research, with a qualitative approach. This research is important as a consideration in the development of attractions, which are the main sector in Wakatobi Regency. Mangrove species that dominate throughout the Wakatobi region are Rhizophora spp, Avicennia spp. and Sonneratia spp. Based on the potential of each island in Wakatobi Regency, Kaledupa Island is a priority area to be developed into ecotourism. This study recommends the construction of several supporting facilities for ecotourism on Kaledupa Island. Suggestions and infrastructure include service facilities, trade facilities and accommodation facilities